Exercícios físicos para adolescentes com sobrepeso a obesidade: Impacto nas variáveis metabólicas e antopométricas relacionadas a síndrome metabólica - Maria Tereza Nicolau dos Santos (2009)
Introduction: Adolescent obesity and sedentary life, cardiovascular disease risk factors, have taken alarming epidemic proportions. Among the several organic implications already found in obese adolescents, the metabolic syndrome stands out. Although the definition of this conditionin children and adolescents is controversial, clinical and laboratory alterations must be monitored. As regular practice of physical exercises is an important and accessible intervention, the aim of this study was to evaluate the impact of an aerobic exercises program that lasted 12weeks on metabolic and anthropometric variables related to metabolic syndrome in overweight or obese adolescents followed up by an interdisciplinary group. Methods: This was a longitudinal clinical trial comparative of parallel groups involving 32 overweight or obese adolescents, divided in 2 groups. The adolescents allocated in the control group (CG, n=17, 6 boys, 11 girls; 13,29 ± 2,22 years of age) participated in fortnight reunions of an interdisciplinary group consisted of pediatrician, physical therapist, psychologist and nutritionist during 12 weeks. The adolescents allocated in the test group (TG, n=15; 7 boys, 8girls; 12,73 ± 2,37 years of age) participated not only in those fortnight reunions, but also in a supervised aerobic exercises program (moderate intensity, 12 weeks, 3 times a week, 60 min). Weight, height, BMI, waist circumference, systolic and diastolic blood pressure (SBP and DBP),fasting glucose and insulin, HOMA-IR, triglycerides, total cholesterol (TC) and its fractions were obtained before and after the intervention period and statistically analyzed by means comparison through Student T-test.Results: The CG showed increases in weight, height, BMI, waist circumference, triglycerides, TC and VLDL-c (p<0,05). The TG showed decreases in BMI, waist circumference, SBP and increases in height and TC (p<0,05). The difference between the groups was significant for weight, height, BMI, waist circumference and SBP alterations (p<0,05).Discussion: Aerobic exercises have positive effects on metabolic and anthropometric variables related to metabolic syndrome in overweight or obese adolescents, optimizing interdisciplinary approach. Physical activity must be encouraged, in order to contribute for a healthier future.